The Effect of Principal’s Management and Teacher’s Performance on Student’s Learning Interests - Seri, Herman; Samsilayurni, Samsilayurni; Agustina, Mediarita (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This study aimed at determining the effect of principal management, teacher performance on students' interest in learning. This research uses quantitative methods. The population of this study were students of State Elementary School 79, State Elementary School 88 and State Elementary School 83 in the Jakabaring area of Palembang City specifically for class VI, totaling 468. The sample was taken 216 from 468 respondents. The data collection technique used a questionnaire. Based on the results of the study, there was a significant influence between the management of the school’s principal and the performance of the teachers together on student’s learning interest. It can be seen from the ANOVA test or F-test, that principal’s management and teacher’s performance have a significant effect on interest in learning. So, the interest in learning can be improved significantly by principal’s management and teacher’s performance. This means that the higher of the quality school principal's management and the higher of the teacher's performance level, will grow the student's interest in learning.